Performance testing with JMeter 2.9 - Erinle, Bayo (Packt Pub., 2013)
Performance Testing With JMeter 2.9 is a standard tutorial that will help you polish your fundamentals, guide you through various advanced topics, and along the process help you learn new tools and skills. This book is for developers, quality assurance engineers, testers, and test managers new to Apache JMeter, or those who are looking to get a good grounding in how to effectively use and become proficient with it. No prior testing experience is required.